Cost Economies and Market Power: The Case of the U.S. Meat Packing Industry - Paul, Catherine J. Morrison (The Review of Economics and Statistics, 2001)
Increasing size of establishments and resulting concentration in U.S. industries may stem from various types of cost economies. In particular, scale economies arising from technological factors embodied in plant and equipment may be a driving force for such market structure changes. In this case, typical market power measures like Lerner indices can be misleading: if scale (cost) economies prevail, cost efficiencies rather than market deficiencies may actually underlie the observed patterns. In this study, I provide measures of scale economies and market power for the U.S. meat packing industry, whose increased consolidation and concentration have raised great concern in policy circles. The results suggest that this trend has been motivated by cost economies, but that little excess profitability exists, and on the margin the potential for taking further advantage of such economies has become minimal.